The effects of ammonium loading rates and salinity on ammonium treatment of wastewater from super-intensive shrimp farming - Tran Manh Hai,; Nguyen Thanh Tung,; Nguyen Trieu Duong,; Nguyen Cam Tu,; Nguyen Truong Quan,; Nguyen Hoai Chau, (Vietnam Journal of Science and Technology, 2023)
Treatment of wastewater from super-intensive shrimp farming (SISF) for discharge or recirculation purposes is currently attracting the attention of managers and researchers. The fixed bed biofilm reactor (FBBR) has been successfully used for biological treatment of drinking water as well as for wastewater treatment in aquaculture farm. Ammonium and salinity are important factors affecting the efficiency of pollutants treatment. This paper presents the results of research on ammonium treatment in super-intensive shrimp wastewater by aerobic microbiological process using FBBRs. The results showed that at ammonium loading rates of 0.014; 0.028; 0.049 and 0.070 kg/m3/d, at salinity of 10‰, the ammonium removal efficiencies  were 98 - 99; 97.7 - 98.8; 96.8 – 98.7 and 95.7 – 98.0 percent respectively (ammonium concentrations in effluent were 0.05 – 0.1; 0.12 – 0.23; 0.23 – 0.56 and 0.51 – 1.07 mgN/l, respectively), at salinity of 15‰, the ammonium removal efficiencies  were 95.8-96.0, 94.5-92.0, 93.1-92.3 and 66.8-68.8 percent respectively  (ammonium in effluent were 0.20 – 0.21; 0.55 – 0.8; 1.20 – 1.35 and 7.8 – 8.3 mgN/l, respectively), at salinity of 20‰, the ammonium removal efficiencies were 92.0-96.0, 87.0-89.0, 69.1-70.9 and 59.6-66.0 percent respectively (ammonium in effluent were 0.2 – 0.4; 1.1 – 1.3; 5.1 – 5.4 and 8.5 – 10.1 mgN/l, respectively). This result showed that the influence of ammonium loading and salinity on ammonium treatment efficiency was very significant.